Pollinator Habitat Conservation Along Roadways, Volume 14: Southeast - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 14: Southeast, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Southeast Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 6: Hawaii - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 6: Hawaii, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Hawaii Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. This is the first of 16 volumes. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 7: Inland Northwest - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 7: Inland Northwest, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Inland Northwest Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. This is the first of 16 volumes. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 9: Mid-Atlantic - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 9: Mid-Atlantic, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Mid-Atlantic Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. This is the first of 16 volumes. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 4: Great Basin - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for the agency and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 4: Great Basin, from TRB's National Cooperative Highway Research Program, is part of a 16-volume series, with each volume focused on a specific region of the United States, and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Great Basin Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 16: Southwest - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 16: Southwest, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Southwest Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains

Pollinator Habitat Conservation Along Roadways, Volume 15: Southern Plains - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 15: Southern Plains, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Southern Plains Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 11: Northeast - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 11: Northeast, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Northeast Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. This is the first of 16 volumes. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 10: Midwest - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 10: Midwest, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Midwest Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. This is the first of 16 volumes. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 3: Florida - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for the agency and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 3: Florida, from TRB's National Cooperative Highway Research Program, is part of a 16-volume series, with each volume focused on a specific region of the United States, and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Florida Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. The other volumes are: Volume 1: Alaska Volume 2: California Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 5: Great Lakes - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 5: Great Lakes, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Great Lakes Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 12: Northern Plains - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 12: Northern Plains, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Northern Plains Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. This is the first of 16 volumes. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 2: California - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for the agency and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 2: California, from TRB's National Cooperative Highway Research Program, is part of a 16-volume series, with each volume focused on a specific region of the United States, and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of California Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. The other volumes are: Volume 1: Alaska Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 8: Maritime Northwest - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 8: Maritime Northwest, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Maritime Northwest Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. This is the first of 16 volumes. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Alaska Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. This is the first of 16 volumes. The other volumes are: Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 13: Rocky Mountains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Pollinator Habitat Conservation Along Roadways, Volume 13: Rocky Mountains - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Transportation agencies can make a difference for imperiled pollinators by managing existing roadside vegetation and designing new revegetation plantings with habitat needs in mind. This can generate public support for agencies and help to mitigate the negative ecological effects of roads. NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 13: Rocky Mountains, from TRB's National Cooperative Highway Research Program, is a 16-volume series. Each volume focuses on a specific region of the United States and is intended to provide relevant guidance to rights-of-way owners and operators for roadside vegetation management practices that support pollinators, as well as strategies that are compliant with the federal Endangered Species Act. Supplemental to the document are a Dataset of Rocky Mountains Accessory Materials, a Communications Toolbox, a Conduct of Research Report, and a Video. All the other volumes are available on the webpage for NCHRP Web-Only Document 362: Pollinator Habitat Conservation Along Roadways, Volume 1: Alaska. The other volumes are: Volume 1: Alaska Volume 2: California Volume 3: Florida Volume 4: Great Basin Volume 5: Great Lakes Volume 6: Hawaii Volume 7: Inland Northwest Volume 8: Maritime Northwest Volume 9: Mid-Atlantic Volume 10: Midwest Volume 11: Northeast Volume 12: Northern Plains Volume 14: Southeast Volume 15: Southern Plains Volume 16: Southwest

Status of Pollinators in North America - National Research Council (The National Academies Press, 2007)
Pollinators2014insects, birds, bats, and other animals that carry pollen from the male to the female parts of flowers for plant reproduction2014are an essential part of natural and agricultural ecosystems throughout North America. For example, most fruit, vegetable, and seed crops and some crops that provide fiber, drugs, and fuel depend on animals for pollination. This report provides evidence for the decline of some pollinator species in North America, including America's most important managed pollinator, the honey bee, as well as some butterflies, bats, and hummingbirds. For most managed and wild pollinator species, however, population trends have not been assessed because populations have not been monitored over time. In addition, for wild species with demonstrated declines, it is often difficult to determine the causes or consequences of their decline. This report outlines priorities for research and monitoring that are needed to improve information on the status of pollinators and establishes a framework for conservation and restoration of pollinator species and communities.

Considerations for Establishing and Maintaining Successful Pollinator Programs on Airports - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Global reports of bee declines have fueled efforts to reduce threats to pollinators and raise public awareness of bees as pollinators of our food crops and native plants. Some airports have implemented pollinator-friendly practices and programs that restore habitat for bees and bring public awareness and appreciation to these fascinating insects. The TRB Airport Cooperative Research Program's ACRP Synthesis 119: Considerations for Establishing and Maintaining Successful Pollinator Programs on Airports summarizes experiences and best management practices of pollinator-friendly programs at airports, particularly beekeeping programs and pollinator habitat management programs.

Evaluating the Suitability of Roadway Corridors for Use by Monarch Butterflies - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Roadsides provide promising monarch habitat as they frequently contain nectar and host plants; however, they also present a range of risks, including pesticide spillover, vehicle collisions, contaminant runoff, and non-native vegetation.The TRB National Cooperative Highway Research Program's NCHRP Research Report 942: Evaluating the Suitability of Roadway Corridors for Use by Monarch Butterflies provides guidance for roadside managers to determine the potential of their roadway corridors as habitat for monarch butterflies.The report also includes several tools and decision-support mechanisms to optimize habitat potential in a manner that is compatible with the continued operation and maintenance of the roadside.